COVID‐19 and the gender gap in work hours - Collins, Caitlyn; Landivar, Liana Christin; Ruppanner, Leah; Scarborough, William J. (Gender, work, and organization, 2021)
School and day care closures due to the COVID‐19 pandemic have increased caregiving responsibilities for working parents. As a result, many have changed their work hours to meet these growing demands. In this study, we use panel data from the US Current Population Survey to examine changes in mothers’ and fathers’ work hours from February through April 2020, the period of time prior to the widespread COVID‐19 outbreak in the United States and through its first peak. Using person‐level fixed effects models, we find that mothers with young children have reduced their work hours four to five times more than fathers. Consequently, the gender gap in work hours has grown by 20–50 per cent. These findings indicate yet another negative consequence of the COVID‐19 pandemic, highlighting the challenges it poses to women’s work hours and employment.